2022
DOI: 10.3390/medicina58091186
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Risk Pulmonary Embolism: A Review of Contemporary Diagnosis, Risk Stratification and Management

Abstract: Pulmonary embolism (PE) can have a wide range of hemodynamic effects, from asymptomatic to a life-threatening medical emergency. Pulmonary embolism (PE) is associated with high mortality and requires careful risk stratification for individualized management. PE is divided into three risk categories: low risk, intermediate-risk, and high risk. In terms of initial therapeutic choice and long-term management, intermediate-risk (or submassive) PE remains the most challenging subtype. The definitions, classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…A study involving 62 institutions on IVCF placement indicated thrombosis in 78 cases (1.3%) [50] . A meta-analysis concluded that IVCF placement plays a role in reducing the short-term risk of subsequent PE but increases the long-term risk of VTE; thus, IVCF should be retrieved as soon as it is no longer needed [47,51] .…”
Section: Management Of Vte In Tbi Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study involving 62 institutions on IVCF placement indicated thrombosis in 78 cases (1.3%) [50] . A meta-analysis concluded that IVCF placement plays a role in reducing the short-term risk of subsequent PE but increases the long-term risk of VTE; thus, IVCF should be retrieved as soon as it is no longer needed [47,51] .…”
Section: Management Of Vte In Tbi Patientsmentioning
confidence: 99%
“…However, the initiation of anticoagulation therapy should not be unnecessarily delayed, and there is no evidence to support using IVCF as an adjunct to anticoagulant therapy [39,40] . Studies indicate that IVCF placement signi cantly reduces the risk of recurrent PE, increases the risk of DVT, but does not signi cantly affect overall mortality regardless of lter use [40,[45][46][47] . Complications associated with IVCF include thrombosis, IVC penetration, perforation, lter fracture, or migration [47,48] .…”
Section: Management Of Vte In Tbi Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-risk APE, which constitutes less than 10% of cases, demands urgent reperfusion therapy to avert imminent mortality [ 5 ]. Although systemic thrombolysis is recommended for these patients, the actual application is limited due to the high risk of haemorrhagic complications or the presence of contraindications in a significant subset of patients [ 6 ]. Furthermore, about 8% of those treated with systemic thrombolysis experience delayed therapeutic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Among hemodynamically stable patients, PE is considered low-risk if there is no evidence of right heart strain, and intermediate-risk in the presence of right heart strain identified through imaging, cardiac biomarker, and/or echocardiographic changes. PE is classified as high-risk when there is hemodynamic instability [ 5 ]. Appropriately categorizing a patient with PE as high-risk, intermediate-risk, or low-risk at the time of their presentation is uniquely impactful for early triage and treatment decisions.…”
Section: Introductionmentioning
confidence: 99%